Surface Roughness Study On Mild Steel In Conventional Turning Process Under Three Condition Cutting Fluids - Abdullah, Abd Halimnizam (2019)
Surface integrity is the surface condition of a workpiece after being modified by a manufacturing process and it can change the material’s properties. In surface topography, surface roughness (Ra) was concerned with the geometry of the outmost layer of the workpiece texture and interface exposed with the environment affects several functional attributes of parts, such as friction, wear and tear, heat transmission, ability of distributing and holding a lubricant, etc. Therefore, the desired surface finish was usually specified and appropriate processes were required to assess and maintain the quality of a component. The research was to investigate the influence of machining parameters and optimum process parameter to the surface roughness value of mild steel material in conventional turning using CVD (chemical vapor deposition) coated carbide insert in three condition (dry, wet and oil). Optimization of the cutting parameters is very important in determine the optimum cutting condition thus reduce machining cost and time consumed. From the results obtained, better surface roughness value was determined by combination of cutting speed 150 m/min, and feed rate 0.1 mm/rev with under coolant oil condition. Tags from this library: No tags from this library for this title.